MORAL DEVELOPMENT OF GRADE IV ELEMENTARY SCHOOL STUDENTS BASED ON KOHLBERG'S THEORY - Utami, Ratna Jayatri (Kopertis Region IV Jabar and Banten, 2024)
This study aims to measure the level of moral development of grade IV students based on Kohlberg's theory. The subjects of this study consisted of one 11-year-old elementary school student who was male. The research uses qualitative research methods. The results showed that elementary school children aged 11 years were generally included in the pre-conventional stage. Based on the results of data analysis, it can be seen that 11-year-old children are still at the pre-conventional stage 1, which tend to want to do something not because they need results but because they are afraid of punishment. This corresponds to the stage of Kohlberg's Theory, namely at the Pre-conventional level, the stage of punishment orientation.